2017
DOI: 10.4172/2167-0420.1000394
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Delivery Service Utilization and Associated Factors among Women of Child Bearing Age at Boset Woreda, Oromia Regional State, Central Ethiopia

Abstract: Background: Evidence has shown access to skilled attendance at birth averting nearly 16-33% maternal deaths. Despite concerted effort to increase access and importance of institutional delivery in preventing maternal death, only 46% and 15% of developing nations and Ethiopian national deliveries, respectively delivered in health facilities that makes assessment of the barriers to health facility delivery important in the study setup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 19 publications
6
23
1
Order By: Relevance
“…3 However, by 2030 global target to reduce maternal mortality ratio to less than 70 per 100,000 live births, working towards a vision of ending all preventable maternal mortality. 4 Three maternal delays are identified as the main contributing factors for maternal mortality and morbidity in many developing countries. Ethiopia, the causes of maternal morbidity and morbidity are similar to many developing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 However, by 2030 global target to reduce maternal mortality ratio to less than 70 per 100,000 live births, working towards a vision of ending all preventable maternal mortality. 4 Three maternal delays are identified as the main contributing factors for maternal mortality and morbidity in many developing countries. Ethiopia, the causes of maternal morbidity and morbidity are similar to many developing.…”
mentioning
confidence: 99%
“…By aligning with health extension program activities like user-fee exemption for institutional delivery service, maternity waiting home service, by availing ambulance service to reach a health facility for childbirth and community mobilization endeavors since July 2005 have been conducted in Ethiopia. [2][3][4] Despite these efforts to increase institution-based delivery service in the country, only 26% of births were attended by skilled birth attendants (SBA). Skilled birth attendants play an important role in reducing maternal and neonatal mortality because they provide timely obstetric and newborn care for life-threatening complications.…”
mentioning
confidence: 99%
“…Finally, 43 studies were screened for full-text review and 24 were included to the prevalence and/ or associated factors analysis (Figure 2). Seven (7) Studies were found in Amhara region [23,24] [25][26][27][28][29], Nine (9) in Oromia [30][31][32][33][34][35][36][37][38], two in Afar [39,40], one in Bienishangul-Gumuz [41] ,three(3) in Southern Nation Nationalities and Peoples region (SNNPR) [42][43][44],one in Gambiela [45] and one in Tigray&Oromiya [46].…”
Section: Study Characteristics and Study Participantsmentioning
confidence: 99%
“…The prevalence of institutional delivery service utilization of individual studies was range from 12.1% to 80.1% [28,29].The seven included studies from Amhara region, which was conducted at different period of time shows that the prevalence of institutional delivery service utilization was 74.7%,34.0%,62.3%,78.8%,15.7%,12.1%, and 80.1% [23][24][25][26][27][28][29].The nine included studies from Oromiya region, which was conducted at different period of time shows that the prevalence of institutional delivery service utilization was 28.7%,13.9%,34.2%,39.7%,12.3%,47.0%,18.2%,16.4%, and 60.3% [30][31][32][33][34][35][36][37][38]. Three included studies from SNNPR region, which was conducted at different period of time shows that the prevalence of institutional delivery service utilization was 14.6%, 31.0% and 78.3% [42][43][44].…”
Section: Prevalence Of Institutional Delivery Service Utilizationmentioning
confidence: 99%
See 1 more Smart Citation